Foregrounding as a Stylistic Strategy for Political Critique in Lasisi Olagunju’s Cowries of Blood - AJALA, Adeola Toyosi; ADEYANJU, Adewumi Raphael; OSOBA, Oluwafikayo Samuel (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
Cowries of Blood by Lasisi Olagunju is a poignant collection of essays addressing the grave security threats facing Nigeria. The book criticises the socio-political scenery of ‘Nigeria, addressing issues such as herdsmen violence, banditry, and what the author terms Nigeria’s endgame politics’. While concentrating majorly on Northern Nigeria, Cowries of Blood is a strong means of portraying and expressing concern about the country’s challenges through a rich tapestry of linguistic features. The paper presents a stylistic analysis of selected essays from Lasisi Olagunju’s Cowries of Blood, focusing on more prominent, defamiliarised and deviant from the norm to attract attention and create aesthetic effects. Key stylistic elements such as foregrounding, metaphor, irony, and satire are skilfully utilised by the author to highlight issues of corruption, violence, and societal decay. Analysing nine essays in Cowries of Blood using Crystal and Davy’s (1969) stylistics approach, the author’s use of language, rhetorical devices, and narrative techniques contributed to the thematic concerns and persuasive power of language in the book. The study concluded that Olagunju’s mastery of language and literary techniques enhances the persuasiveness of his socio-political commentary and engages readers in a critical reflection on the issues facing Nigeria.